Insurance theory and practice - Thoyts, Rob. (Milton Park, Abingdon, Oxon : New York : Routledge, 2010)
Presents a comprehensive overview of the theory, functioning, management and legal background of the insurance industry. This title begins with an examination of the insurance concept, its guiding principles and legal rules before moving on to an analysis of the market, its players and their roles and relationships.
Includes bibliographical references and index.
Keywords: Insurance; Social Science